Mediamorphosis of Betawi Cultural Broadcasting Domain Into New Media Domain - SHAHAB, Fauziah (PT Keberlanjutan Strategis Indonesia, 2023)
Along with the development of technology and the internet, mediamorphosis has affected the domain of broadcasting Betawi culture, which was initially limited to traditional media such as radio and television, shifting to new media domains such as the internet and social media. This mediamorphosis significantly impacts the promotion, representation, and understanding of Betawi culture among the public. This study aims to analyze the mediamorphosis from the broadcasting domain of Betawi culture to the domain of new media by paying attention to disruption and changes in the representation and accessibility of Betawi culture. The research method used is media analysis, which involves collecting data from various new media sources containing Betawi cultural content. The study results show that the morphosis of media from the Betawi cultural broadcasting domain to the new media domain has expanded the reach and accessibility of Betawi culture. Betawi cultural content can now be accessed via digital platforms such as websites, apps, and social media. Mediamorphosis changes the way Betawi culture is disseminated, accessed, and understood by society and also helps revitalize Betawi culture.